2015 54th IEEE Conference on Decision and Control (CDC) 2015
DOI: 10.1109/cdc.2015.7402279
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance rejection via control by interconnection of port-Hamiltonian systems

Abstract: In this paper we present a new result on rejection of unmatched external disturbances on port-Hamiltonian systems using Control by Interconnection (CbI). The PHS structure is used to design a controller that rejects unmatched constant disturbances from non-passive outputs. In the PHS framework, the disturbance rejection problem has been addressed adding integral action and using a change of coordinates. In our approach, we avoid a change of coordinates keeping the original state vector, which contains variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Proposition 1: Consider system (10) subject to unknown, matched disturbance in closed loop with the controller (11). Then, under Assumptions 1-6, the equilibrium of the closed loop, corresponding to the gradient (16), is globally asymptotically stable.…”
Section: Matched Disturbancementioning
confidence: 99%
“…Proposition 1: Consider system (10) subject to unknown, matched disturbance in closed loop with the controller (11). Then, under Assumptions 1-6, the equilibrium of the closed loop, corresponding to the gradient (16), is globally asymptotically stable.…”
Section: Matched Disturbancementioning
confidence: 99%
“…In [5] it is shown that pH systems with convex Hamiltonian are also shifted passive provided the input, dissipation and interconnection matrices are all constant. Conditions for shifted passivity of pH systems with state-dependent matrices have been reported in [6] and [21]. In the former case, quite conservative, integrability conditions, are imposed while the latter ones are too general and thus can be difficult to verify.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the control system studied in [14] has a physical interpretation and is shown to be equivalent to a control by interconnection (CbI) scheme, another PBC technique [15]. The method in [13] was shown to be applicable to mechanical systems with constant mass matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we extend the integral action design proposed in [13] to underactuated mechanical systems subject to matched disturbances. The assumption of a constant mass matrix is relaxed, and general mechanical systems are considered.…”
Section: Introductionmentioning
confidence: 99%